ANALISIS EFEKTIVITAS TEKNIK DISPUTING IRRATIONAL BELIEFS DALAM MENINGKATKAN SELF-ACCEPTANCE YANG RENDAH SEBAGAI UPAYA MENGURANGI TINDAKAN SELF-BLAME: SUATU KAJIAN LITERATUR - Kirana Ula Muzhaffarah; Dina Nurul Ilmi; Prayitno, Nasywa Anandhita; Mila Yunita (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2025)
Self blame often arises when someone has difficulty accepting themselves and has unrealistic ways of thinking. Low self acceptance makes individuals prone to seeing mistakes as a reflection of themselves, leading to irrational beliefs such as feeling less fortunate than others or always failing. This pattern then reinforces the habit of self blame. This study used a literature review method, examining various articles and journals related to self acceptance, irrational beliefs, self blame, and the use of the Disputing Irrational Beliefs (DIB) technique. The literature reviewed came from relevant national and international studies. The results of the study show that the DIB technique helps individuals test and challenge irrational beliefs so that their thinking becomes more rational. The reduction in irrational beliefs increases self acceptance, which ultimately reduces the tendency to self blame. Thus, the DIB technique can be an effective approach to increasing self acceptance in reducing self blaming behaviour.